Comparison of Lung Capacity in Communities in Low Land and High Land - Norma Juniati; Syamsul Bahri; Yenni Desimarlina; Annisa Zikri Robbia; Ainun Jariah; Husnul Fuadi (Jurnal Biologi Tropis, 2021)
The environment in which they live has a major influence on the development of a person's physical characteristics and abilities. One of the physical capacities that is strongly influenced by the anthropometric measurements of the body and the body's adaptability to the environment is the vital capacity of the lungs. The vital capacity is the maximum volume of air that can enter and leave the lungs during one breathing cycle after maximum inspiration and maximum expiration. This study aims to determine the difference in the vital capacity of the lungs in the people in the lowlands of Mataram city and the highlands of Sembalun village. Sampling was done using purposive sampling technique with a sample of 20 people in each research area with an age range of 21-25 years. The data were collected using a simple spirometer made by the researcher. The control variables in this study included gender, age, height, body weight and sample hemoglobin levels. The results showed the average value of vital lung capacity in the lowlands was 2837.5 ml, while the vital capacity of the lungs in the highlands was 2767.5 ml. The results of hypothesis testing were carried out using the Independent Sample t-test using SPSS 16 and the results of the significance value (2-tailed) 0.740> 0.05 so that Ho was accepted, which means that there is no difference in the vital capacity of the lungs in the highlands and lowlands.